2022
DOI: 10.1208/s12249-022-02422-6
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Permeation Studies on Carvedilol Containing Dissolving Microarray Patches Quantified Using a Rapid and Simple HPLC-UV Analytical Method

Abstract: Analytical method validation is a vital element of drug formulation and delivery studies. Here, high-performance liquid chromatography in conjunction with UV detection (HPLC-UV) has been used to produce a straightforward, quick, yet sensitive analytical approach to quantify carvedilol (CAR). A C18 column was used to isolate the analyte from the mixture by isocratic elution with a mobile phase comprising a mixture of 0.1% v/v trifluoroacetic acid in water and acetonitrile in a ratio of 65:35 v/v at a flow rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…DMAPs individually loaded with either FITC‐dextran 150 kDa or fluorescein sodium exhibited a height reduction percentage of less than 20%, which suggested that the needles had desirable hardness and mechanical strength to penetrate the skin [ 18 ] ( Figure a). Eight layers of Parafilm were folded to reach a total height of ≈1000 µm, with the thickness for each sheet about 126 µm.…”
Section: Resultsmentioning
confidence: 99%
“…DMAPs individually loaded with either FITC‐dextran 150 kDa or fluorescein sodium exhibited a height reduction percentage of less than 20%, which suggested that the needles had desirable hardness and mechanical strength to penetrate the skin [ 18 ] ( Figure a). Eight layers of Parafilm were folded to reach a total height of ≈1000 µm, with the thickness for each sheet about 126 µm.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of each drug was quantified using the HPLC method at intervals of 1, 2, 3, 7, 14, 21, and 28 days. 59…”
Section: Methodsmentioning
confidence: 99%
“…As a rule, chromatographic methods are used to fulfill the selectivity requirement. Usually, the most used types of detectors are UV or diode array [ 83 , 84 , 85 , 86 , 87 ], fluorescence [ 88 , 89 ], and mass spectrophotometry [ 90 , 91 , 92 ], depending on the nature of the analyzed drug.…”
Section: Methods Involving the Quantification Of Nano-entrapped Drugsmentioning
confidence: 99%